2003
DOI: 10.1109/tmtt.2002.806922
|View full text |Cite
|
Sign up to set email alerts
|

An improved multiline analysis for monolithic inductors

Abstract: This paper presents a new efficient multiline model for monolithic inductors. A preliminary model was developed by Huynen, which divided the spiral in sections of coupled transmission lines whose parameters are calculated by a variational principle. This model has been improved for inductors with high trace width-to-gap ratios and it has been demonstrated to be adequate for predicting -parameters characterizing the inductor over a wide frequency band, even above its self-resonant frequency. This new design too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Simulations are performed using an analytical model [14, 15] for frequencies from 0.5 to 15 GHz. Calculations consider the FMR of nanowires involved in the formula of relative permeability of the substrate, as explained in next section, dielectric losses of alumina membrane depending of porosity, the coupling between strips of the meander inductor, and the skin depth effect from aluminum electrodes.…”
Section: Topology and Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulations are performed using an analytical model [14, 15] for frequencies from 0.5 to 15 GHz. Calculations consider the FMR of nanowires involved in the formula of relative permeability of the substrate, as explained in next section, dielectric losses of alumina membrane depending of porosity, the coupling between strips of the meander inductor, and the skin depth effect from aluminum electrodes.…”
Section: Topology and Operationmentioning
confidence: 99%
“…Recently, Yupapin et al [13,14] have shown the promising idea that the nonlinear effects of light in fiber optic of microring resonators. In this work, the simple system of the attosecond pulse generation using the integrated optic devices known as the multistage microring resonators is proposed [15]. The large bandwidth signal can be generated within the microring device by using a light pulse input into the nonlinear microring resonator and filter referred to as an add/drop filter the characteristics of complementary ring resonator modeling [16].…”
Section: Introductionmentioning
confidence: 99%
“…A lumped circuit model of on-chip spiral inductor grown on Si substrate is shown in Figure 2 [9][10][11]. L S and r S are the series inductance and resistance of the spiral respectively.…”
Section: Modeling Of Spiral Inductormentioning
confidence: 99%
“…The approaches, such as using high resistivity substrate and high conductive metal layers, thick dielectric layer or selectively etching off substrates, stacking metal layers [7,8], and even differentially driven inductors, have been reported [9,10]. However, no systematic study on the performance trend of spiral inductors with temperature has been reported in the literature, except in [11].…”
Section: Introductionmentioning
confidence: 99%